PERILAKU BERTELUR DAN SIKLUS HIDUP Aedes aegypti PADA BERBAGAI MEDIA AIR - Indira Agustin; Udi Tarwotjo; Rully Rahadian (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2017)
Aedes aegypti is the main vector that transmits dengue fever. The spread of Aedes aegypti mosquitos in Indonesia is very wide. This mosquito has its breeding site in clear water areas such as in the bath water containers, flower pots, pet containers as well as in the used goods that can hold stagnant water. However, the environmental conditions which are constantly changing due to the rampant pollution cause Ae. Aegypti to continue to adapt to its breeding environment. This research aims to find out the egg laying behavior, life cycle and mediums preferences selected by Aedes aegypti mosquitos in different water mediums. Stages of the research which are conducted include: preparation of research tools and materials, observation on Ae. Aegypti mosquitos’ preferences, observation on egg hatchability and life cycle of Ae. Aegypti in various water mediums. The result shows that from all contaminated water mediums which are tested, Ae. Aegypti mosquitos have the preference of laying eggs in Eichhornia crassipes water mediums, followed by leachate water mediums, whereas in tofu wastewater mediums and laundry waste, there were no eggs found. Meanwhile, in another study, it is known that the egg hatchability and life cycle of Ae. Aegypti mosquitos in contaminated water mediums such Eichhornia crassipes immersed water mediums, and leachate water are not significantly different from controlled water mediums (uncontaminated). The result of the research is expected to be the reference for relevant institute in expanding the eradication of Ae. Aegypti mosquitos to places that have been unusual for eradication.Keywords: Aedes aegypti, Eichhornia crassipes immersed water, Leachate, laundry waste, tofu wastewater